1998
DOI: 10.1175/1520-0469(1998)055<3244:asttfd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Thermodynamical Theory for Dust Devils

Abstract: Based on the heat engine framework, a simple scaling theory for dust devils is proposed and compared to observations. This theory provides a simple physical interpretation for many of the observed characteristics of dust devils. In particular, it predicts the potential intensity and the diurnal variation of dust devil occurrence. It also predicts that the intensity of dust devils depends on the product of two thermodynamic efficiencies, corresponding respectively to vertical and horizontal temperature gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
272
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(290 citation statements)
references
References 15 publications
(20 reference statements)
15
272
0
2
Order By: Relevance
“…Further, atmospheric modeling (Tyler and Barnes 2013; suggested that the depth of the daytime boundary layer inside the crater is suppressed. This suppressed, shallow depth was expected to reduce vortex activity, or at least vortex intensity, since the thermodynamic efficiency of vortices depends upon the boundary layer depth according to the so-called heat engine model (Renno et al 1998(Renno et al , 2000. Nevertheless, an extensive campaign of imaging Dust Devil Search Movies was initiated after MSL's landing (Moores et al 2015).…”
Section: Mars Science Laboratory/curiosity Rovermentioning
confidence: 99%
“…Further, atmospheric modeling (Tyler and Barnes 2013; suggested that the depth of the daytime boundary layer inside the crater is suppressed. This suppressed, shallow depth was expected to reduce vortex activity, or at least vortex intensity, since the thermodynamic efficiency of vortices depends upon the boundary layer depth according to the so-called heat engine model (Renno et al 1998(Renno et al , 2000. Nevertheless, an extensive campaign of imaging Dust Devil Search Movies was initiated after MSL's landing (Moores et al 2015).…”
Section: Mars Science Laboratory/curiosity Rovermentioning
confidence: 99%
“…They assumed that individual dust devils lift dust at a rate of 0.7 × 10 −3 kg m −2 s −1 , based on field measurements of dust concentration and vertical wind speed in dust devils (Kaimal and Businger 1970;Renno et al 2004). They then used the thermodynamic theory for dust devils of Renno and Ingersoll (1996) and Renno et al (1998) to estimate the fractional area over which dust devils should be active. The theory developed by Renno et al (1998) describes a convective vortex (dust devil) as a heat engine that performs mechanical work against frictional dissipation.…”
Section: Scaling Dust Fluxes Based On Field Measurements Of Individuamentioning
confidence: 99%
“…They then used the thermodynamic theory for dust devils of Renno and Ingersoll (1996) and Renno et al (1998) to estimate the fractional area over which dust devils should be active. The theory developed by Renno et al (1998) describes a convective vortex (dust devil) as a heat engine that performs mechanical work against frictional dissipation. Driven by this convective heat engine, the dust devil activity, F av , is approximated by…”
Section: Scaling Dust Fluxes Based On Field Measurements Of Individuamentioning
confidence: 99%
See 1 more Smart Citation
“…In this latter case, shear stress is not the lifting mechanism. Instead light grains are drawn vertically by rising air driven by an atmospheric convective instability reacting to the inversion of a warm air mass below a cooler mass [Renno et al, 1998]. …”
Section: Martian Atmospheric Dustmentioning
confidence: 99%